Poptella fuscata, a new Stethaprionini from the upper Amazon basin, Peru (Characiformes: Characidae) - Garcia-Ayala, James R. [UNESP]; Benine, Ricardo C. [UNESP] (Wiley, 2021)
A new species of Poptella is described from the Río Putumayo, Upper Río Amazon basin, Peru. The new species is distinguished from congeners by having a dense field of dark chromatophores homogeneously spread over the posterior half of the body, posterior humeral blotch extending to three to four horizontal scale rows below the lateral line, and a higher number of branched dorsal-fin rays. The new species can be readily distinguished from P. paraguayensis by having a comparatively shorter predorsal spine.
Keywords: biodiversity; freshwater fishes; neotropical; Río Nanay; Río Putumayo; taxonomy